Adsorptive Removal and Recovery of U(VI) from Single Component Aqueous Solutions by Sugarcane Bagasse Impregnated with Magnetite Nanoparticles - Saeid Alamdar Milani; Borhan Rahnamay Moghadam; Ahmad Khodadadi Darban (مجله علوم و فنون هسته‌ای, 2014)
A magnetic biosorbent composed of nanoparticles of magnetite covered with sugarcane bagasse and denominated magnetic baggas was prepared. The magnetic composite was used to remove U(VI) ions from aqueous solutions. The magnetite was synthetized by simultaneous precipitation by adding a solution of NaOH to the aqueous solution containing Fe2+ and Fe3+. The magnetic bagasse presented superparamagnetic properties; that is, it showed a high magnetization of saturation without hysteresis. The magnetic bagasse was characterized by XRD and SEM techniques. Nitrogen adsorption/desorption analysis on magnetic bagasse showed a nanostructure with an average particle size of 34 nanometers, with a specific surface area of 102.3 m2 g-1, and average pore diameter of 6.23 nm. Its adsorption performance was evaluated by determining the adsorption capacity of U(VI) ions by means of batch method. The results indicated that the biosorption capacity was significantly affected by the pH solution, biosorbent dosage, contact time, and initial uranium concentration. The uranium binding by the biomass test was rapid, and achieved 92% of the sorption efficiency within 20 min. The optimum biosorption (97.4%) was observed at pH 4.0, biosorbent dosage of 5 mg/L, initial uranium concentration of 50 mg L-1 within 90 minutes. The maximum adsorption capacity of the magnetic bagass for U(VI) ions was at biosorbent dosage of 1 g L-1 and obtained to be 32.04 mg g-1. The kinetic data were fitted well to a pseudo-second-order rate equation (R2=0.9996). The adsorption process conformed the Langmuir and Dubinin-Radushkevitch (D-R) adsorption isotherm models. Gibbs free energy (DG°) and enthalpy change (DH°) indicated that the reaction had been spontaneous and exothermic in nature at the studied temperatures. In the desorption studies, 94.5% of  adsorbed U(VI)wasrecoverd with hydrochloric acid as an eluent.